Modification of electronic properties of graphene with porphyrin self-assembled monolayers and photoinduced interactions - Khaderbad, Mrunal A. (2013)
Solution processable reduced graphene oxide (RGO), with its unique electrical and structural properties is being considered in large scale device fabrication. The research developments in the formation and characterization of nanoelectronic devices with self-assembled monolayers (SAMs) of porphyrin can have foundations for future high speed electronics, alternative energy sources and sensors. In this work, we present the effect porphyrin monolayer functionalization on the electronic properties of RGO. Electrical transport measurements show that this dipolar monolayer on RGO induces doping and the capacity to tune the electronic properties of RGO may have important applications in future graphene devices, sensors and energy harvesting. Also, carrier transfer from excited zinc porphyrin molecules to carbon-based nanostructures is demonstrated on transistors comprising physiosorbed RGO on zinc porphyrin SAM.